Seismic Stability of Loess Tunnel with Rainfall Seepage - Xuansheng Cheng; Wanlin Zhang; Jing Fan; Xiaoyan Zhang; Haibo Liu; Xinhai Zhou (Advances in Civil Engineering)
Rainfall seepage changes the mechanical properties of loess masses. Considering fluid-solid coupling, the calculation model of a loess tunnel is established according to the finite element method (FEM). Based on porous media seepage theory and rainfall infiltration depth theory and considering the infiltrated depth of the loess surface for different rainfall intensities over a certain period, the stability of a loess tunnel under different rainfall amounts and loess cover thicknesses is studied using the dynamic finite element static strength reduction method. The results show that under the same rainfall intensity, the safety factor increases with the depth of the tunnel; the safety factor of the loess tunnel with the same loess cover thickness decreases with increasing infiltration depth. The plastic strain is mainly distributed on both sides of the vault and the arch feet. The stability of the loess tunnel is directly related to the loess cover thickness and rainfall seepage.